Editorial - Margherita Azzari (Bollettino della Società Geografica Italiana)
The «Bollettino della Società Geografica Italiana» is the oldest geographical journal in Italy and one of the first to be published in the world. Its first issue came out in 1868. Since then it has never interrupted publication, even during the most dramatic moments of the two world wars. The «Bollettino» is thus 150 years old. This is a most important anniversary that is worth celebrating with a substantial renewal of the journal, though remaining committed to its original spirit and features. This is a challenge we want to face, knowing that it requires hard work, commitment and balance. The most important innovation is its move to digital open access: a decision taken in order to increase the degree of sharing and dissemination of substantial, original research focussing on geographical issues from different theoretical and methodological perspectives, traditionally one of the prerogatives of our journal...